A spatial investigation into the colonial landscapes of sex in Johannesburg, Durban, and Cape Town, c. 1860 - 1910 - O’Shea, Siobhan Reanne (My University, 2022)
In the late-19th and early-20th centuries British-colonial South Africa had several thriving sex industries. Sex work was an active feature in the illicit economies of Johannesburg, Durban, and Cape Town from their respective inceptions. Such 19th and 20th century sex work has been studied archaeologically since the 1980s in North America, but equivalent sustained work has not been conducted on contemporaneous South African sex work. With a focus on their respective spatial formations, the aim of this dissertation was to assess whether Johannesburg, Durban, and Cape Town’s sex industries were contained within distinct red-light districts between 1860 and 1910. In addition, I aimed to determine the visibility of sex workers and their own voices within the South African colonial archive. I generated spatial data that can be used for future archaeological investigation and identified potential material markers for identifying sex work-related sites. This was achieved for Johannesburg by producing a Google Earth map of brothel addresses acquired from the National Archives in Pretoria. Durban and Cape Town maps were produced using historiographical literature. Photographs of sex workers and pimps preserved in the colonial archive provided clues towards the potential materiality of sex work in South Africa, and the manner in which sex workers were criminalised in the colonial legal system
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Sex workers; South African sex work; Photographs of sex workers